Conservancies as a development tool in Zimbabwe's CAMPFIRE Districts - Muzvidziwa, Victor N. (2016)
In Zimbabwe conservancies could be the engines for sustainable economic growth through the establishment of viable eco-tourism infrastructure. Conservancies offer an innovative approach to rural development. They present possibilities for the establishment of co-managed collaborative ecotourism in business ventures involving rural communities. Conservancies have demonstrated that benefits can flow to rural communities on the basis of co-managed wildlife resources. Through conservancies community empowerment and regional development in the context of Zimbabwe's CAMPFIRE districts is possible. This paper supports the view that the main strategy for conservancies should be conservation through utilization. Conservancies are capable of embarking on self-sustaining eco-tourism operations that seek to promote the conservation and sustainable use of rangelands. The paper's main argument is that conservancies as tenurial units can turn wildlife and other attractions to products that can be utilized to effect sustainable wildlife driven rural development for as long as the basic principles of eco-tourism development are followed.